False-positive screens and lung cancer risk in the National Lung Screening Trial: Implications for shared decision-making. (June 2018) - Pinsky, Paul F; Bellinger, Christina R; Miller, David P
Objectives: Low-dose computed tomography lung cancer screening has been shown to reduce lung cancer mortality but has a high false-positive rate. The precision medicine approach to low-dose computed tomography screening assesses subjects' benefits versus harms based on their personal lung cancer risk, where harms include false-positive screens and resultant invasive procedures. We assess the relationship between lung cancer risk and the rate of false-positive LDCT screens. Methods: The National Lung Screening Trial randomized high-risk subjects to three annual screens with low-dose computed tomography or chest radiographs. Following the completion of National Lung Screening Trial, the Lung CT Screening Reporting and Data System (Lung-RADS) classification system was developed and retrospectively applied to National Lung Screening Trial low-dose computed tomography findings. The rate of false-positive screens (by Lung-RADS) and the resultant invasive procedures were examined as a function of lung cancer risk estimated by a model. Results: Of 26, 722 subjects randomized to the low-dose computed tomography arm, 26, 309 received a baseline screen and were included in the analysis. The proportion with any false positive over three screening rounds increased from 12.9% to 25.9% from lowest to highest risk decile, and the proportion with an invasive procedure following a false positive also significantly increased from 0.7% to 2.0% from lowest to highest risk decile. Conclusion: These findings indicate a need for personalized low-dose computed tomography lung cancer screening decision aids to accurately convey the benefits to harm trade-off.